Improving Outcomes in Pancreatic Adenocarcinoma: A Systematic Review of Immunotherapy in Multimodal Treatment - Paul-Cristian Borz; Mihnea Bogdan Borz; Oliviu-Cristian Borz; Toader Zaharie; Claudia Hagiu; Lidia Munteanu; Simona Gurzu (Medicina)
Background: Despite advances in chemotherapy and supportive care, pancreatic ductal adenocarcinoma (PDAC) continues to carry a dismal prognosis, with a five-year survival rate of approximately 13%. While immunotherapy has revolutionized treatment for several malignancies, its efficacy in PDAC remains limited. Recent research has shifted focus toward integrating immunotherapy with chemotherapy, radiation, and targeted therapies in an effort to overcome therapeutic resistance and improve outcomes. Ongoing clinical trials are actively investigating these multimodal strategies. Materials and Methods: A systematic search was conducted using PubMed and ScienceDirect to identify relevant studies published in the past six years. Search terms included “pancreatic adenocarcinoma immunotherapy,” “pancreatic cancer treatments,” and “combination treatments for pancreatic adenocarcinoma.” Only English-language articles were included. Results: A total of 126 articles were initially identified through the database search. After a full-text screening, 48 articles were deemed potentially relevant. Following a rigorous review, 11 studies met the inclusion criteria and were selected for analysis. These studies included randomized controlled trials, non-randomized controlled trials, and retrospective studies. Meta-analyses and case reports were excluded. Articles that failed to meet the inclusion criteria were excluded, primarily due to the absence of relevant data addressing the main objective of this review. Conclusions: Combination strategies with immunotherapy and chemotherapy offer modest survival gains in metastatic settings, yet efforts in resectable and borderline resectable disease have fallen short. These outcomes reflect the profound immunosuppressive forces of the PDAC microenvironment. A new era of treatment must move beyond broad immunotherapeutic applications toward a precision-driven model. Molecular markers, such as KRAS mutations and circulating tumor DNA (ctDNA) profiles, are beginning to illuminate paths for personalized therapy selection. Future progress will depend on biomarker-guided clinical trials, a deeper understanding of immune resistance mechanisms, and bold innovation at the intersection of immunology and tumor biology.